The Effect of Tongue Twister Drill Technique on Students Speaking Skill - Farih, Abdullah; Hamdiyah, Henny (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
The purpose of this study is to determine students learning outcomes using tongue twister drill in teaching speaking for students of SMA Manggala Sakti Dadapan Solokuro. This research is experimental research. The sample of this study was the tenth-grade students of SMA Manggala Sakti Dadapan Solokuro, totalling 23 students. Data was collected through tests consisting of pre-test and post-test. The results of this study indicated that the experiment conducted by the researcher on the students was able to influence by using a test which consisted of several questions. So, the average value of the pretests is 61,32. while the post-tests have an average value of 75,32. The results of this study indicate that the experiment conducted by the researcher on eleventh grade students using a small group discussion in teaching speaking skill was able to influence student learning outcomes. It was proved by the value of t-test (,000) which was < 0,05. It indicated that there was significant, this is also indicated Ha was accepted and H0 was rejected. Based on the finding the teacher must employ a range of strategies. Drilling was recommended as a technique that English teachers should implement when teaching speaking skill. The teacher also should give variety of teaching strategies